Gambaran Karakteristik Pasien Stroke yang Mengalami Konstipasi Pasca Rawatan: Characteristics of Stroke Patients with Constipation Post-treatment - Maria Valentina Sibarani; Rahmi Ulfah; Esi Afriyanti (Fakultas Keperawatan Universitas Andalas, 2019)
Constipation is a problem that is often complained of by stroke patients, if not addressed will lead to complications of other diseases. The purpose of this study was to see a description of the characteristics of stroke patients who experience post-treatment constipation. This type of research is descriptive, the number of samples of 54 people taken by simple random sampling. The quosioener used to screen stroke patients is the National Institute of Health Stroke (NIHSS) and the Constipation Scoring System (CSS) for screening patients who experience constipation. The frequency distribution test results are more constipation suffered by women (68.52%), junior high school education (50%), history of IRT work (37.04%), average age of 53 years, stroke duration of 63 months and long time using laxative 23 months. Conclusion:Post-treatment stroke patients often experience constipation caused by disorders of the autonomic nerve and long-term use of laxatives. In addition,constipation in post-treatment stroke patients is influenced by female sex, increasing age, low educational status, IRT employment and duration of stroke. Post treatment stroke patients to reduce the use of laxatives and replace with more consumption of fiber and fluids and sufficient activity, to minimize the incidence of constipation.